Five‐year study of quality of life in myotonic dystrophy. (21st December 2015) - Peric, S.; Vujnic, M.; Dobricic, V.; Marjanovic, A.; Basta, I.; Novakovic, I.; Lavrnic, D.; Rakocevic‐Stojanovic, V.
Abstract : Background – Myotonic dystrophy type 1 (DM1) is the most common muscular dystrophy in adults. There is a complete lack of studies that assessed quality of life (QoL) trajectory during time in DM1 cohorts. Aim – To analyze changes of QoL in patients with DM1 during a 5‐year follow‐up period and to assess responsiveness of the SF‐36 questionnaire. Patients and Method – At the baseline, this study comprised 84 DM1 patients, of whom 62 were retested after the mean period of 64.2 ± 3.9 months. Severity of muscular weakness was assessed using the Muscular Impairment Rating Scale (MIRS). Patients completed Serbian version of the SF‐36 questionnaire as a measure of health‐related QoL. Results – After 5 years, MIRS score of our DM1 patients showed significant progression of 0.5 grade ( P < 0.01). All mental subdomains, role physical, and total SF‐36 scores significantly improved after 5 years ( P < 0.01). Unexpectedly, worsening of muscular weakness from mild to severe was in association with improvement of QoL. Conclusion – QoL improved in our cohort of DM1 patients during a 5‐year period despite the progression of the disease. SF‐36 should be used with caution as a patient‐reported outcome measure in DM1 clinical trials.